Altered States of Rurality: Cultural Forays into Southern Ontario Country - Walden, Riisa (My University, 2011)
This dissertation examines contemporary cultural representations of rurality in southern Ontario. It demonstrates how literary and cultural texts construct, support and/or expand our understandings of the social composition and character of rural culture. Examining various literary forms (drama, life narrative, and the novel), music, and photography, my research and analysis responds to Chris Philo’s pivotal call in the field of rural geography “to pay more careful attention to ‘the multiple forms of otherness’ present in . . . rural areas” (“Neglected” 199) and to foreground what he identifies as “neglected rural geographies.” I argue that dominant literary and cultural representations of rural southern Ontario overwhelmingly mobilize and rarely contest white heteromasculinist rural discourses that support rural cultures of sameness and exclusion. As a means of exposing the motivations for and deleterious effects of these discourses, I draw attention to alternative representations of the region’s rural social geography that expand the imaginative scope circumscribed by hegemonic conceptualizations of what it means to be rural in southern Ontario. As such, my project responds to Philo’s call in three ways: first, it repositions southern Ontario as a rural locale of critical relevance; second, it addresses a gap in Canadian literary and cultural studies by taking up new and evolving approaches in rural studies, with respect to rural “others,” being developed in disciplines like geography, sociology, history and political science; third, it intervenes in dominant socio-spatial discourses currently circulating in Canadian literary and cultural studies that eagerly address issues of gender, sexuality, race and class in Canada’s urban environments while too often neglecting how they intersect with discourses of rurality.
Keywords: rurality; southern Ontario; multiculturalism; critical race studies; gender and sexuality studies; Canadian literature and culture; Feminist, Gender, and Sexuality Studies; Lesbian, Gay, Bisexual, and Transgender Studies; Literature in English, North America; Literature in English, North America, ethnic and minority; Modern Literature; Other Music; Other Race, Ethnicity and post-Colonial Studies; Visual Studies; Feminist, Gender, and Sexuality Studies